Examining the Effects of the RUNX1 p.Leu43Ser Variant on FPD/AML Phenotypes Using a CRISPR/Cas9-Generated Knock-In Murine Model - Ana Marin-Quilez; Ignacio García-Tuñón; Rocío Benito; José Luis Ordoñez; Lorena Díaz-Ajenjo; Ana Lama-Villanueva; Carmen Guerrero; Jesús Pérez-Losada; José Ramón González-Porras; Jesús María Hernández-Rivas; Mónica del Rey; José María Bastida (Biomolecules)
Germline heterozygous variants in RUNX1 lead to Familial Platelet Disorder with Myeloid Leukemia Predisposition (FPD/AML). Cellular and/or animal models are helpful to uncovering the role of a variant in disease progression. Twenty-five mice per genotype (RUNX1WT/WT, RUNX1WT/L43S, RUNX1L43S/L43S), previously generated by CRISPR/Cas9, and nine sub-lethally irradiated mice per genotype were investigated. Peripheral blood (PB), bone marrow (BM), and spleen samples were analyzed by flow cytometry and histopathology. Deregulated genes were analyzed by RNA-seq in BM. An aberrant myeloid Mac1+Sca1+ckit− population in the PB, BM, and spleen of two homozygous and one heterozygous mouse was observed, as well as BM hypercellularity. No Mac1+Sca1+ckit− cells were detected in any RUNX1WT/WT mice. Moreover, the spleen of both homozygous mice showed destruction of the white/red pulp and the presence of apoptotic cells. The aberrant population was also detected in four irradiated mice, two heterozygous and two homozygous, in their PB, BM, and spleen. RNA-seq studies showed 698 genes significantly deregulated in the three non-irradiated Mac1+Sca1+ckit− mice vs. six healthy mice, highlighting the alteration of genes involved in apoptosis and DNA repair. These results indicate that the homozygous form of the variant p.Leu43Ser may contribute to the pathogenesis of aberrant cells.